Morphological, Electrical, and Chemical Characteristics of Poly(sodium 4-styrenesulfonate) Coated PVDF Ultrafiltration Membranes after Plasma Treatment - Ivette G. Sandoval-Olvera (Polymers, 2019)
A commercial ultrafiltration (UF) membrane (HFM-183 de Koch Membrane Systems) made of poly(vinylidene fluoride) (PVDF), was recovered with a negatively-charged polyelectrolyte (poly(sodium 4-styrenesulfonate)) (PSS), and the effects on its electric, chemical, and morphological properties were analyzed. Atomic force microscopy (AFM), liquid−liquid displacement porometry, Electrical Impedance Spectroscopy, X-ray photoelectron spectroscopy, and Raman spectroscopy were used to investigate the modifications induced by the deposition of PSS on the PVDF positively-charged membrane and after its treatment by a radio frequency Ar-plasma. These techniques confirmed a real deposition and posterior compaction of PSS with increasing roughness and decreasing pore sizes. The evolution of the electric resistances of the membranes confirmed crosslinking and compaction with shielding of the sulfonated groups from PSS. In this way, a membrane with a negatively-charged active layer and a pore size which was 60% lower than the original membrane was obtained. The composition of the additive used by manufacturers to modify PVDF to make it positively charged was obtained by different procedures, all of which depended upon the results of X-ray photoelectron spectroscopy, leading to fairly consistent results. This polymer, carrying positive charges, contains quaternary nitrogen, as confirmed by XPS. Moreover, Raman spectroscopy confirmed that PVDF changes from mostly the β to the α phase, which is more stable as a substrate for the deposited PSS. The aim of the tested modifications was to increase the retention of divalent anions without reducing permeability.